Substituição do milho por glicerina bruta na dieta de caprinos - Borges, Gisele Daiana Silveira (2014)
In order to evaluate the effects of adding levels of crude glycerin replacing corn in the diet of goats on intake, digestibility and ruminal diets containing zero, six, 12 and 18% crude glycerin were tested. The diets were composed of 55 % concentrate and 45% roughage (hay Tifton 85). Using four fistulated Boer goats and four intact on a double 4x4 Latin square. The intake and digestibility of dry matter, organic matter and fiber NDF did not differ among treatments in g/day and %BW, as did the consumption of hay and concentrate. The consumption of protein, ADF and ether extract responding quadratic and linear treatments to positive and negative manner, respectively, in g/day and % BW. The consumption of protein had a quadratic effect in g / day and did not change in % BW. The ADF digestibility increased linearly in % BW. Nitrogen balance and pH did not differ among treatments. The ruminal pH and ammonia nitrogen showed significant differences depending on the time of collection. The ammonia nitrogen also showed linear decrease with increasing levels of glycerin. The results of this study show that the use of crude glycerin replacing corn in the diet of goats, up to the level of 18% does not cause negative effects on consumption, diet digestibility, rumen pH and nitrogen balance. The ammonia nitrogen decreases with increasing levels of glycerin, however, remains at appropriate levels for ruminal activity.